Piece of Cake: News in Easy Language - Angelou, Evlambia (International Journal of Linguistics and Translation Studies, 2025)
The increasing linguistic diversity for reasons of interculturality, education, age, mental skills, etc., at the international level creates the need for information available in many languages and at a different linguistic level. Usually, linguistic accessibility- translation- is more often presented as a "right" only to the extent that it is necessary to protect other rights (ex. access to legal services). Barriers to information intake arise when, for example, a person can take in the information but does not have sufficient command of the language in which the information is written. This paper aims to highlight the use of easy language as a key tool for effective information communication in the news, making information related to current events accessible and adapted to the needs of people who, for various reasons, have a limited understanding of the official/dominant language.